Stone Vessels and Values in the Bronze Age Mediterranean - Bevan, Andrew (Cambridge University Press, 2013)
This book first began as doctoral research, for which I benefited from generous financial support from the Arts and Humanities Research Council (then AHRB). During this time, I was able to conduct fieldwork and attend conferences largely through the further support of the Institute of Archaeology, the University College London (UCL) Graduate School, and the British Institute of Archaeology at Ankara, to all of whom I am extremely grateful. A Leverhulme Trust postdoctoral fellowship, while dedicated to other research goals, allowed time for me to acquire additional skills and to develop my ideas further. Thereafter, I was able to devote a crucial year to new research and writing-up with the benefit of an Institute of Aegean Prehistory fellowship, a Cotton Foundation grant, and a Michael Ventris Memorial Fund award, all of which led to late insights into particularly thorny problems. The final stages of writing were challenged and yet also inspired by the demands of full-time teaching at UCL.